A case cluster of possible tissue invasive gonorrhoea. Issue 2 (April 1995) - Brook, M G; Clark, S; Stirland, A; Kelsey, M C; Paice, E W; Kell, P D; Atia, W A
Abstract : OBJECTIVE--To describe a cluster of patients presenting with severe symptoms and infected with an unusual strain of Neisseria gonorrhoeae. SETTING--A north London Department of Sexual Health. PATIENTS--Five patients were linked by reported sexual contact or other epidemiological evidence as part of a cluster of gonococcal infection. Cultured N gonorrhoea were subtyped by serological (serovar) and cultural (auxotype) methods and antibiotic sensitivities measured by minimum inhibitory concentration (MIC). RESULTS--Four of the patients had severe gonorrhoea-related systemic or extragenital symptoms: disseminated gonococcal infection with oligoarthritis (1 patient), acute pelvic inflammatory disease (1 patient, who was also chlamydia positive) and tender inguinal adenopathy (2 patients). The fifth patient was asymptomatic. N gonorrhoeae was isolated in four of the patients. All four organisms had identical MICs. Three of the organisms were subtyped and found to be the same rare strain (serovar 1A1, auxotype NR). CONCLUSION--This case cluster provides evidence for strain-related virulence in an uncommon gonococcal subtype.